Sorptional behaviour of rosehip leather formulations added with sucrose or polydextrose - Demarchi, Silvana María (2014)
The sorptional behaviour of two formulations intended to develop rosehip leathers, both based on rosehip fruit pulp, was assessed experimentally. One formulation had sucrose added, while polydextrose was added to the other to reduce the calorie intake. Isotherms were measured by the static gravimetric method at 10, 20, 40 and 60 °C. The GAB equation and a model proposed by Leiva Díaz, Giannuzzi, and Giner (2009) gave the best representation of data for sucrose- and polydextrose-added formulations, respectively. A detailed statistical analysis revealed an interaction between composition and temperature effects on isotherms. Sucrose proved to be more effective than polydextrose to lowering the water activity of the formulation, except in conditions that favour the formation of sucrose crystals. In general, the water activity of the polidextrose-added formulation, which did not experience crystallisation, increased with increasing temperature for a given moisture content. However, the temperature effect on the isotherms of the sucrose-added matrix was more complex, possibly being affected by crystallisation.